Managing Rural Landscapes in the Context of a Changing Climate - Kutter, Andrea (Taylor and Francis, 2014)
Global competition for natural resources is intense and the supply of those resources is increasingly more constrained by climate variability and change. Governments and international development agencies have the dual responsibility to meet the socioeconomic needs of the poorest and most vulnerable people while preserving and enhancing their natural capital. These responsibilities often are at odds with each other and different stakeholder groups have prioritized one over the other. This paper suggests that the landscape approach provides a solution for stakeholders to achieve climate change mitigation, adaptation, and poverty reduction goals, though not without some trade-offs.